Cavity spectral-hole-burning to boost coherence in plasmon-emitter strong coupling systems. (19th November 2022) - Zhou, Wen-Jie; You, Jia-bin; Xiong, Xiao; Lu, Yu-Wei; Ang, Lay Kee; Liu, Jing-Feng; Wu, Lin
Abstract: Significant decoherence of the plasmon-emitter (i.e., plexcitonic) strong coupling systems hinders the progress towards their applications in quantum technology due to the unavoidable lossy nature of the plasmons. Inspired by the concept of spectral-hole-burning (SHB) for frequency-selective bleaching of the emitter ensemble, we propose 'cavity SHB' by introducing cavity modes with moderate quality factors to the plexcitonic system to boost its coherence. We show that the detuning of the introduced cavity mode with respect to the original plexcitonic system, which defines the location of the cavity SHB, is the most critical parameter. Simultaneously introducing two cavity modes of opposite detunings, the excited-state population of the emitter can be enhanced by 4.5 orders of magnitude within 300 fs, and the attenuation of the emitter's population can be slowed down by about 56 times. This theoretical proposal provides a new approach of cavity engineering to enhance the plasmon-emitter strong coupling systems' coherence, which is important for realistic hybrid-cavity design for applications in quantum technology.